The National Character of Image of Childhood in Artistic Heritage of Writers-Enlighteners of the Second Half of the XIXth Century - Pobirchenko, Nataliya (Pedagogical Discourse, 2011)
The artistic heritage of writers-enlighteners of the second half of the XIXth century, which is filled with the problems of national character of image of childhood is analysed in the article. The nature of childhood is disclosed through traditions and standards of breeding in family. The structure of the inner world is shown through the emotional impressions of environment, family surroundings, world of science and others like that. The thing, which promots the rendering of culture heritage from generation to generation and helps the child to learn the history of traditions, customs of own nation, provides inward connection between generations.